Regional variation in agro-morphological descriptors of Sesbania bispinosa (Jacq.) W. Wight - Chanda, Sontosh C; Hossain, Md Amir; Rahman, Md Mustafizur; Shamsuzzaman, ANM; Sarwar, AKM Golam (Bangladesh Journal of Botany, 2019)
The effect of regional diversity on 12 agro-morphological descriptors of Sesbania bispinosa (Jacq.) W. Wight was studied. The mean sum of square varied significantly for six of these traits viz., plant height, branch number/plant, pod number/plant, pod length, seed number/pod and seed width. Among the ten regions, plants grown from seeds of Tangail, Chuadanga and Sirajganj districts of Bangladesh performed better in terms of plant height, number of branches/plant, number of pods/plant, pod length, number of seeds/pod and seed width. In principal component analysis, first six principal components (PC1, PC2, PC3, PC4, PC5 and PC6) showed Eigen value >1 and accounted for 85.6% of the total variance. In cluster analysis based on the studied agro-morphological descriptors, the cluster 1 consists of three regions (Chuadanga, Tangail and Jhinaidah), cluster 2 of six regions (Khulna, Mymensingh, Rangpur, Sunamganj, Gaibandha and Faridpur) and cluster 3 of only one district (Sirajganj). Considering these multivariate analyses, three different morphotypes of S. bispinosa could be identified from different locations.